Effect Of Sop Implementation And Ppe Usage On Needle Puncture Incident On Nurses In Rsud Siti Fatimah South Sumatera Province - Muhammad Rizkian Elsaputra; Mika Vernicia Humairo (Journal of Hospital Management and Services, 2022)
Needlestick injuries in healthcare workers are a significant problem in healthcare institutions today it is estimated that more than one million needles are used each year by nurses. When a nurse accidentally stabs herself with a needle that has previously entered the patient's body tissue, the nurse is at risk of contracting hepatitis B (HBV), as well as Human Immunodeficiency Virus (HIV). This study was conducted by quantitative methods with cross sectional observation research design, based on these problems this study was used to see whether the effect of the application of SOP and the use of PPE on the incidence of work accidents in RSUD Siti Fatimah South Sumatra province. And the results showed that the application of SOP is good with a value of 52.0% along with the results of logistic regression analysis showed a p value of 0.024 < 0.05 then reject H0, while the observance of the use of PPE is also good with a value of 68.8% along with the results of logistic regression analysis showed a p value of 0.012 < 0.05 then reject H0, and the incidence of pinprick work accidents has experienced 13 people (10.4%). So based on the table R Square can be seen that the application of SOP and the use of PPE has an effect with a value of 0.416 (41.6%).